2021
DOI: 10.1159/000520630
|View full text |Cite
|
Sign up to set email alerts
|

Electromotive Drug Administration of Mitomycin C (EMDA/MMC) versus Intravesical Immunotherapy with Bacillus Calmette-Guérin (BCG) in Intermediate and High Risk Non Muscle Invasive Bladder Cancer

Abstract: <b><i>Background:</i></b> Although TURB of tumor (TURBT) by itself can eradicate a non-muscle-invasive bladder cancer (NMIBC) completely, these tumors commonly recur and can progress to MIBC. It is, therefore, necessary to consider adjuvant therapy in most patients. The primary objective of the present study was to report our experience with EMDA/MMC and BCG, considering efficacy, progression, and recurrence, as adjuvant therapy in NMIBC patients; the secondary objective was to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Short-term (10 months) oncologic results after EMDA [24 ▪▪ ] in comparison to BCG showed a statistical significant lower recurrence rate in favor of EMDA (14.3% (20 pts.) vs. 24% (25 pts.…”
Section: Evidence Synthesismentioning
confidence: 93%
See 2 more Smart Citations
“…Short-term (10 months) oncologic results after EMDA [24 ▪▪ ] in comparison to BCG showed a statistical significant lower recurrence rate in favor of EMDA (14.3% (20 pts.) vs. 24% (25 pts.…”
Section: Evidence Synthesismentioning
confidence: 93%
“…Nine studies that investigated HIVEC (oncological outcomes were reported for 1137 patients and AEs for 970 patients) were included for final evaluation after fulfilling the inclusion criteria [13 ▪▪ ,14 ▪▪ ,15 ▪▪ ,16 ▪▪ ,17 ▪▪ ,18 ▪▪ ,19 ▪ ,20 ▪▪ ,21 ▪▪ ]. Another three studies were additionally analyzed: two of them reported outcomes after radiofrequency-induced HIVEC [22 ▪▪ ,23 ▪▪ ], and one after EMDA [24 ▪▪ ]. A summary of the most frequently used devices for intravesical administration of chemotherapy and their characteristics are presented in Table 1.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This electromotive technology improved the uptake of mitomycin C after instillation compared with passive transport [ 93 , 94 ], and a 5-year and 10-year cost-effectiveness study concluded that electromotive mitomycin C administration is a cost-effective treatment for patients with high-risk NMIBC [ 95 ]. Electromotive drug administration represents a viable option in patients with BCG-unresponsive NMIBC and reduces the risk of NMIBC recurrence [ 96 , 97 ]. A recent study comparing the efficacy of radiofrequency-induced mitomycin C therapy and electromotive mitomycin C administration showed no differences in the recurrence-free rate at 12 months, toxicity, and adverse effects [ 98 ].…”
Section: Colloidal Nano- and Micro-sized Delivery Systemsmentioning
confidence: 99%
“…EMDA protocols adopted by the various centers show slight variations, with earlier studies using a lower current amplitude of 15 mA over shorter time periods of 20 min, while most subsequent studies utilize a maximum of 20 to 23 mA of pulsed DC applied over a duration of 30 min [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. No differences in tolerability and adverse side effects were observed with the higher amplitude and longer durations.…”
Section: Pre-clinical Studies and Clinical Applications Of Emda In On...mentioning
confidence: 99%